Sport Participation and Psychosocial Factors Which Influence Athletic Identity in Youth Athletes With Anterior Cruciate Ligament Injury - McGinley, James; Stapleton, Emily; Worrall, Hannah; Ellis, Henry B.; Wilson, Philip L.; Ulman, Sophia (Frontiers in Psychology, 2022)
Athletic identity, or the degree with which individuals identify with the athlete role, is an important rehabilitation factor for sports care providers to consider; however, it lacks extensive study in youth. The purpose of this study was to identify demographic, sport participation, and psychosocial measures which correlate with youth athletic identity after anterior cruciate ligament injury. Participants completed standardized sports medicine intake and patient-reported outcome measures, including the Athletic Identity Measurement Scale (AIMS). A total of 226 participants were included, and two groups were created based on high or low total AIMS score. Results indicated that sex (p=0.002), years active in sport (p=0.049), activity level (p=0.038), and ACSI-Coachability (p=0.027) differed by AIMS score. While youth athletes appear resilient, these results emphasize that they identify strongly with the athlete role and may suffer psychosocial consequences after injury. Future work should evaluate similar factors over course of recovery in a larger, diversified population.